A Case Study on the First Language Attrition during the Second Language Acquisition - Anisah Durrotul Fajri (ELITE JOURNAL, 2023)
Immigration has become one of the reasons for an individual to experience a second or foreign language acquisition, but at the same time, it may also result in language loss, or called language attrition. For this reason, conducting research on immigrants may give a broad insight regarding language acquisition and attrition. This study aims to reveal the language attrition experienced by an Indonesian child born in Japan who acquired Japanese as her first language and moved to Indonesia where she acquired her second language but at the same time also lost her first language during the second language acquisition. This study also investigates the reasons behind first language attrition, and the parent’s role to maintain their children’s first language. Qualitative research was conducted by using interview and observation techniques to gather information regarding the process of attrition. Overall, the study offers insight into how fast language attrition can happen to a child. This study further reveals the causes of first language attrition which include the language proficiency of the child at the onset of attrition, the decrease of the first language input, the increase of the second language input, and the language proficiency of the parent. Keywords: first language attrition, language acquisition, language attrition, second language acquisition